Right to convert a child: a study on the legal standing in Malaysia / Amir Fitri Mohd Yusoff ... [et al.] - Mohd Yusoff, Amir Fitri; Ismail, Amalina; Awang Kechik, Afifah Munirah; Azli, Aida Khairuleen; Md Isa, Noor Aqilah (2010)
The long existing misunderstanding over the religious status of minors when one of the parents converts to Islam has brought greater confusions among the people and has drawn criticisms from both Muslims and non-Muslims through the decisions of the court in a number of cases over the years and the recent proposed policy by the government as to the determination of religion of the child. This is due to lack of understanding of the legal standing in Malaysia in relation to the right to convert a child for which this project paper intends to promote. This is done by first clarifying the issue before hand through the conceptual understanding of right to convert a child. Having done that, we will proceed by identifying and anaylising the legal standing and relates it to the practice in Malaysia with reference to local Civil and Syariah Laws and decided cases. We will continue to discuss the effect of child conversion on other related issues such as the child's position, custody, maintenance and inheritance to evaluate the relationship between the right to convert a child and those issues before one could determine and justify who and why he/she should have such right. In the end of this project paper, conclusion will be made and recommendations will be proposed based on the findings of the research with the hope to promote a better and clearer understanding on the issue and reduce intensity among the multi-religious community in this country.